Soft Skills for the Professional Services Industry : Principles, Tasks, and Tools for Success. - Creutzmann, Andreas (John Wiley & Sons, Inc., 2022)
Soft Skills for the Professional Services Industry Auditors, accountants, lawyers, consultants, and other highly educated and trained professionals frequently hold impressive credentials and offer clients specialized expertise in complex areas. At the same time, these professionals understandably focus on the analytical and technical components of their jobs, sometimes to the point of excluding or ignoring important soft skills critical to the success of their careers and practices. In Soft Skills for the Professional Services Industry: Principles, Tasks, and Tools for Success, veteran auditor and entrepreneur Andreas Creutzmann delivers an essential discussion of often overlooked professional competencies that can mean the difference between career, engagement, and business success or failure. In the book, you'll find accessible guidance on critical soft skills that can make a difference between fulfilment and success and failure on a professional and personal level. You'll learn to handle the blending of home and the home office, how to effectively manage staff, how to market yourself and your firm, practical strategies for client and colleague communication, and how to find happiness in your day-to-day work. Each chapter stands alone and can be read in any order. They provide professionals with invaluable skills for navigating the modern--and digital--reality of work, showing you how to combine your professional education with the latest research and common sense on everything from client management to firm marketing. Soft Skills for the Professional Services Industry uses the field of auditing as a template and guide, but it is highly relevant to all skilled professionals - including lawyers, consultants, medical professionals, and others. The book is a must-read for any knowledge worker trying to add to their toolbox of practical skills. Critical guidance for practicing professionals on how to build often overlooked soft skills Most highly educated and trained professionals aren't lacking in analytical or technical skills. Lawyers know the law, accountants understand double entry bookkeeping, and doctors know anatomy. However, many of us are less familiar with often overlooked--and equally essential--soft skills: client management, communication, staff and employee management, and others. In Soft Skills for the Professional Services Industry, accomplished auditor, entrepreneur, and consultant Andreas Creutzmann walks you through how to build critical competencies, from self-marketing to balancing work and life when your office is in your house. The book is made up of numerous, self-contained chapters that can be read in any order, and it demonstrates how to navigate increasingly digital and insistent professional demands on your time, effectively manage client and colleague relationships, and sell new clients on the services your firm offers. An essential roadmap to achieving personal and career success, Soft Skills for the Professional Services Industry is an indispensable resource for lawyers, doctors, accountants, auditors, and any other extensively skilled professional. It offers practical tools in functional areas that are frequently neglected in formal professional training.